Cultural safety nursing education in Canada: a comprehensive literature review - Roy-Michaeli, Monique (2011)
This comprehensive literature review provides a current review of the ways cultural safety is being drawn on in nursing education in Canada. Beginning with a grounding in the conceptualization of culture and its relation to health, this review then explores the history of cultural safety education in New Zealand drawing to light their experiences with implementing a cultural safety framework into their nursing curricula. Theoretical and educational approaches that address power relations, promote social justice, and are congruent with cultural safety will be discussed to establish a link to what has been and is being considered in nursing education to address health inequities and difficult issues such as racism. This paper provides a summary of current literature about educating nurses to provide culturally safe care. The writer reveals what progress has been made but also discusses the implications of the cultural safety framework for educating Aboriginal nursing students, for rural nurses, for the care of First Nations People, and for nursing care in today‟s Canadian multicultural context. Questions for further inquiry and research are also identified. Graduate